The political economy of alternative export-led strategies: Exporting differently? - Riccardo Pariboni; Walter Paternesi Meloni (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
The paper enters the current debate at the intersection of comparative political economy and international trade on the role of price and non-price competitiveness in influencing export. Through an econometric exploration, we identify price competitiveness as a non-negligible factor in driving export, for a set of OECD countries from 1994 to 2019. The documented price sensitiveness, combined with the institutions and policies adopted to promote export-led growth, casts an unsettling light on the prospects for a recovery, particularly for the Euro area. These worrying conclusions are not, however, unescapable. The emergence of the export-led growth model - with its twin brother, the debt-led one - answered the demand-generating problems created by years of wage share decreases and a steady retreat of the State from its traditional demand management role. Drastically inverting these tendencies would contribute to strongly narrowing the need for export-led strategies.
Keywords: E02; P16; O57; 330; comparative political economy; export; export-led growth; price competitiveness; non-price competitiveness; economic crises